Becoming a zero single use plastic nation - Ali, Fathilah (The Star, 2019)
WHAT once seemed impossible to start has begun, what was once a habit that seemed impossible to change has started to turn around. And it all started when Yeo Bee Yin announced her "break-up" with single-use plastic in September 2018.